Mo segregation induction-based superfine heterostructure martensitic steel and heat treatment process thereof

Through the heat treatment process based on Mo partial polymerization-induced heat treatment process, the problems of difficulty in preparing ultrafine heterostructure materials and the problems of reduced strength are solved, and the efficient preparation and excellent strength and toughness of ultrafine heterostructure martensitic steel are achieved in large section size.

CN119464940APending Publication Date: 2025-02-18XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411622231.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The preparation of existing ultrafine heterostructure materials depends on large plastic deformation, which makes it difficult to prepare materials with large cross-sectional sizes and cannot undergo secondary heat treatment, resulting in a decrease in material strength.

Method used

Ultrafine heterostructured martensite steel without large plastic deformation was prepared by preheating treatment, rapid heating and quenching treatment.

Benefits of technology

The controllable preparation of ultra-fine heterostructured materials with large cross-sectional size has been achieved, which significantly improves the strength and toughness of the materials. The yield strength can reach 2000~2500MPa, the tensile strength can reach 2100~2700MPa, and the elongation is 6~12%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464940A_ABST
    Figure CN119464940A_ABST
Patent Text Reader

Abstract

The invention discloses ultrafine heterostructure martensitic steel based on Mo segregation induction and a heat treatment process of the ultrafine heterostructure martensitic steel. The martensitic steel comprises the following chemical components in percentage by weight: 0.4-0.7% of C, 0.3-1.0% of Mn, 1.0-2.0% of Si, 0.2-1.5% of Cr, 0.01-3.5% of Ni, 0.2-0.8% of Mo, less than or equal to 0.03% of P, less than or equal to 0.03% of S and the balance of Fe. The method comprises the following steps: firstly, obtaining a pearlite type structure rich in Mo cementite through a normalizing or tempering process by utilizing the characteristic that Mo element is easily enriched in the cementite; then austenitizing treatment is conducted through a rapid heating technology by means of the characteristics that in the austenitizing process, the dissolving speed of molybdenum-rich cementite is low, and the diffusion speed of the Mo element is low, and a superfine austenite structure with the Mo element distributed unevenly is obtained, that is, a nanometer / submicron Mo-rich area exists in superfine austenite; and then quenching and tempering treatment are carried out, a tempered martensite structure with a superfine heterostructure is obtained, so that excellent strength and plasticity are obtained, the yield strength of the alloy can reach 2000-2500MPa, the tensile strength can reach 2100-2700MPa, and the ductility is 6-12%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-high strength steel, and in particular to an ultra-fine heterogeneous structure martensitic steel based on Mo segregation induction and a heat treatment process thereof. Background Art

[0002] There is an inverse relationship between material strength and plastic toughness, that is, when the strength of a material increases, its plastic toughness often decreases. Therefore, how to achieve a coordinated improvement in the strength and toughness of metal materials is an extremely challenging task. Grain refinement strengthening is considered to be a method that can simultaneously improve the strength and toughness of a material. When the grains are refined to an ultrafine grain scale, the strength of the material can be increased exponentially. However, when the grains are refined to this scale, the material's strain hardening ability will be significantly reduced, which will lead to a significant decrease in the material's plasticity, and the contradiction between the strength and plasticity of the material will still be shown. In order to solve the problem of the restrictive relationship between strength and plasticity in ultrafine-grained metal materials, scholars have proposed the concept of "heterogeneous" metals through a large number of experimental explorations. Through heterogeneous design, more geometrically required dislocations are introduced into the material during the deformation process to improve the material's strain hardening ability, thereby improving the material's strength and toughness.

[0003] "Ultrafine heterogeneity" strengthening and toughening is achieved by introducing two or more component units with significantly different performances into the ultrafine structure to achieve a synergistic improvement in strength and toughness.

[0004] The patent with publication number CN1325685C discloses a heterogeneous material with alternating distribution of martensite laths and austenite films, which significantly improves the comprehensive mechanical properties of the material. In a broad sense, heterogeneity includes heterogeneity between components (such as differences in grain size, crystal structure, crystal orientation or chemical composition, etc.) or intrinsic properties, geometric form, volume fraction, spatial arrangement of component units, etc.; common heterogeneous structures include gradient structure, layered structure, harmonic structure, dual-phase structure, etc.

[0005] However, the current work on improving the toughness of materials by using "ultrafine heterogeneous structure" design is still in the laboratory stage. The main reason is that the preparation of "ultrafine heterogeneous structure" materials currently relies on large plastic deformation, and the deformation temperature is low, and the deformation resistance of the material is large, which makes it difficult to prepare materials with large cross-sectional dimensions. On the other hand, this "ultrafine heterogeneous structure" material that relies on large plastic deformation preparation cannot be subjected to secondary heat treatment. During the secondary heat treatment process, the structure is very easy to coarsen, resulting in reduced material strength. Therefore, how to break through the controllable preparation of "ultrafine heterogeneous structure" materials with large cross-sectional dimensions is the key to realizing its engineering application. Summary of the invention

[0006] In order to overcome the defects of the above-mentioned prior art, the present invention proposes an ultrafine heterostructure martensitic steel based on Mo segregation induction and its heat treatment process, which has the characteristics of not requiring large plastic deformation and being able to prepare "ultrafine heterostructure" materials with large cross-sectional sizes.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] An ultrafine heterogeneous structure martensitic steel based on Mo segregation induction, wherein the Mo element is unevenly distributed in the martensitic steel, and a heterogeneous structure is formed by Mo-rich martensite and Mo-poor martensite, wherein the Mo-rich martensite has higher strength, and the size of the Mo-rich martensite is in the nanometer to submicron order, and the Mo-poor martensite has relatively low strength but better plasticity, thereby forming the ultrafine heterogeneous structure martensitic steel. In terms of weight, the chemical composition (wt%) of the martensitic steel is: C: 0.4-0.7, Mn: 0.3-1.0, Si: 1.0-2.0, Cr: 0.2-1.5, Ni: 0.01-3.5, Mo: 0.2-0.8, P: ≦0.03, S: ≦0.03, and the rest is Fe.

[0009] The Mo-rich martensite has a high density (up to 10 16 / m 3 The above) coherent nano-carbides are precipitated, while the precipitation density of coherent nano-carbides in Mo-poor martensite is relatively low, and the particle size of the coherent nano-carbides is 2-5 nm.

[0010] The ultrafine heterogeneous structure martensitic steel based on Mo segregation induction has a yield strength of 2000-2500 MPa, a tensile strength of 2100-2700 MPa and an elongation of 6-12%.

[0011] A heat treatment process for ultrafine heterogeneous martensitic steel based on Mo segregation induction comprises the following steps:

[0012] Step 1: Pre-heat treatment

[0013] The alloy within the above composition range is subjected to normalizing or quenching and tempering treatment to obtain an alloy having a pearlite-type structure with lamellar or granular Mo-rich cementite;

[0014] Step 2: Rapid heating and quenching

[0015] The alloy with pearlite structure obtained in step 1 is subjected to rapid heating austenitization treatment to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there is a nanometer / submicron size Mo-rich area in the ultrafine austenite; and immediately subjected to quenching treatment to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite and Mo-poor martensite and film-like or granular residual austenite;

[0016] Step 3: Tempering

[0017] The quenched martensite prepared in step 2 is tempered to obtain a tempered martensite structure with ultrafine heterogeneous structural characteristics.

[0018] For the preliminary heat treatment in step 1, it includes the following processes:

[0019] Step 1) Pre-heating

[0020] The alloy material is heated to A in a heating furnace. C3 The temperature is 30-50℃ above the workpiece and the heat preservation treatment is carried out. The heat preservation time depends on the thickness of the workpiece and is determined at 1-1.5min / mm.

[0021] Step 2) Pre-heat treatment cooling

[0022] The alloy material heated in step 1) is taken out of the furnace and air-cooled to room temperature or oil-quenched to room temperature to obtain a pearlite structure or a martensite structure;

[0023] Step 3) Secondary heating treatment during preheat treatment

[0024] The pearlite or martensite structure obtained in step 2) is heated to 600-700°C and kept at this temperature for 1-10 hours, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite type structure with lamellar or granular Mo-rich cementite.

[0025] For lamellar pearlite structure, the treatment at 600-700℃ for 1-10h can provide enough time for the Mo element to diffuse and be enriched in cementite, thus obtaining a pearlite type structure with lamellar Mo-rich cementite.

[0026] For the martensitic structure, keeping the temperature at 600-700℃ for 1 to 10 hours can provide kinetic conditions for the precipitation of carbides on the one hand, and provide sufficient time for the Mo element to diffuse and be enriched in the particulate cementite on the other hand, thus obtaining a pearlite-type structure of particulate Mo-rich cementite.

[0027] The rapid heating and quenching treatment in step 2 includes the following processes:

[0028] Step 1) Rapid heating and austenitization

[0029] The pre-heat-treated pearlite alloy is rapidly heated to A C3 Temperature above 30~80℃ and keep warm for 40~600s, heating rate ≥15℃ / s;

[0030] Due to the slow dissolution rate of Mo-rich cementite and the slow diffusion rate of Mo element, Mo-rich carbides can hinder the coarsening of austenite grains before dissolving during the austenitizing heating process. After the Mo-rich carbides are dissolved, Mo-rich zones will be formed within a certain size range near their original positions. Therefore, an ultrafine austenite structure with uneven Mo element distribution can be obtained, that is, there are nanometer / submicron size Mo-rich zones in the ultrafine austenite.

[0031] Step 2) Quenching

[0032] The alloy after the austenitization treatment is immediately cooled to room temperature by oil quenching to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, namely, Mo-rich martensite, Mo-poor martensite and film-like or granular retained austenite.

[0033] For the tempering treatment in step 3, the process is:

[0034] The ultrafine heterogeneous quenched martensite structure prepared by the above process is tempered at 200-350°C for 1.5-4h to obtain an ultrafine heterogeneous structure tempered martensite structure, in which high-density coherent nanocarbides (carbide size 2-5nm) are precipitated in the nano / submicron-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0035] The alloy designed by the present invention is prepared through the above process, and the ultrafine heterogeneous structure martensitic steel based on Mo segregation induction has excellent strong plasticity: after tempering, the carbides precipitated in the Mo-poor martensite area have a low density and relatively low strength, and can provide plasticity during plastic deformation; while the carbides precipitated in the Mo-rich martensite area have a high density and high strength, which can improve the strength of the material; at the same time, since the size of this heterogeneous structure is small, the difference in strength will not damage the plasticity of the material, so the yield strength of the alloy can reach 2000-2500MPa, the tensile strength can reach 2100-2700MPa, and the elongation is 6-12%.

[0036] The preparation method of the ultrafine heterogeneous martensitic steel proposed in the present invention is based on alloy design and heat treatment regulation and preparation, and does not rely on large plastic deformation, so ultrafine heterogeneous martensitic steel with large cross-sectional size can be prepared.

[0037] Beneficial effects of the present invention:

[0038] 1. The alloy system and heat treatment process designed in the present invention make full use of the element segregation characteristics in the phase transformation process and its influence on the subsequent martensitic phase transformation to prepare ultrafine heterogeneous structure martensitic steel, breaking through the technical bottleneck of the difficulty in preparing ultrafine heterogeneous structure materials with large cross-sectional sizes, and can prepare ultrafine heterogeneous structure martensitic steel with large cross-sectional sizes.

[0039] 2. The ultrafine heterogeneous structure martensitic steel prepared by the present invention has excellent strength and toughness. The yield strength of the material can reach 2000-2500MPa, the tensile strength can reach 2100-2700MPa, and the elongation is 6-12%.

[0040] 3. The ultrafine heterogeneous structure martensitic steel described in the present invention has a simple process route, low requirements on production equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a pearlite type structure with lamellar Mo-rich cementite.

[0042] Figure 2 It is a pearlite type structure with granular Mo-rich cementite.

[0043] Figure 3 It is the ultrafine heterogeneous structure tempered martensite structure after rapid heating quenching and tempering.

[0044] Figure 4 This is a transmission image of the ultrafine heterostructure tempered martensite structure. DETAILED DESCRIPTION

[0045] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0046] Example 1

[0047] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.41, Mn: 0.75, Si: 1.0, Cr: 1.45, Ni: 1.8, Mo: 0.39, P: 0.016, S: ≤ 0.025, and the rest is Fe.

[0048] The heat treatment process includes the following steps:

[0049] Step 1: Pre-heat treatment

[0050] The alloy is heated to 830°C (A C3 The sample was heated to 400℃ and kept at this temperature for 1h (the holding time was determined by 1.0min / mm), then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure; then the sample was heated to 600℃ and kept at this temperature for 8h, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure with lamellar Mo-rich cementite.

[0051] Step 2: Rapid heating and quenching

[0052] The pearlite-type alloy obtained in step 1 was heated to 870°C (A) at a heating rate of 20°C / s. C3 The temperature is above 80°C) and then kept at this temperature for 240s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then it is immediately oil-quenched and cooled to room temperature to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0053] Step 3: Tempering

[0054] The quenched martensite prepared in step 2 is tempered at 300°C for 2h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0055] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2012MPa, the tensile strength can reach 2143MPa, and the elongation is 11.6%.

[0056] Example 2

[0057] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.53, Mn: 0.64, Si: 1.4, Cr: 1.32, Ni: 1.5, Mo: 0.43, P: ≤ 0.03, S: ≤ 0.03, and the rest is Fe.

[0058] The heat treatment process includes the following steps:

[0059] Step 1: Pre-heat treatment

[0060] The alloy is heated to 830°C (A C3 The sample was heated to 50°C (above 50°C) and kept for 1.5h (the holding time was determined by 1.5min / mm), then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure; then the sample was heated to 700°C and kept for 2h, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure with lamellar Mo-rich cementite.

[0061] Step 2: Rapid heating and quenching

[0062] The pearlite-type alloy obtained in step 1 was heated to 850°C (A) at a heating rate of 15°C / s. C3The temperature is above 70°C) and then kept warm for 300s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then it is immediately oil-quenched and cooled to room temperature to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0063] Step 3: Tempering

[0064] The quenched martensite prepared in step 2 is tempered at 250°C for 3h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0065] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2235MPa, the tensile strength can reach 2447MPa, and the elongation is 9.6%.

[0066] Example 3

[0067] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.61, Mn: 0.98, Si: 1.96, Cr: 0.22, Ni: 0.02, Mo: 0.22, P: ≤ 0.03, S: ≤ 0.03, and the rest is Fe.

[0068] The heat treatment process includes the following steps:

[0069] Step 1: Pre-heat treatment

[0070] The above alloy is heated to 840℃ (A C3 The sample was heated to 30°C (above 30°C) and kept for 1.5h (the holding time was determined by 1.5min / mm), then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure; then the sample was heated to 650°C and kept for 6h, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure with lamellar Mo-rich cementite.

[0071] Step 2: Rapid heating and quenching

[0072] The pearlite-type alloy obtained in step 1 was heated to 850°C (A) at a heating rate of 25°C / s. C3 The temperature is 40°C above the preheating temperature and then kept at this temperature for 120s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then the material is immediately cooled to room temperature by oil quenching to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0073] Step 3: Tempering

[0074] The quenched martensite prepared in step 2 is tempered at 250°C for 3h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0075] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2166MPa, the tensile strength can reach 2488MPa, and the elongation is 8.5%.

[0076] Example 4

[0077] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.7, Mn: 0.31, Si: 1.9, Cr: 0.95, Ni: 3.46, Mo: 0.78, P: ≤ 0.03, S: ≤ 0.03, and the rest is Fe.

[0078] The heat treatment process includes the following steps:

[0079] Step 1: Pre-heat treatment

[0080] The alloy is heated to 820°C (A C3 The sample was heated to 500℃ and kept at this temperature for 1.5h (the holding time was determined by 1.2min / mm), then taken out of the furnace and air-cooled to room temperature to obtain pearlite structure; then the sample was heated to 600℃ and kept at this temperature for 10h, then taken out of the furnace and air-cooled to room temperature to obtain pearlite structure with lamellar Mo-rich cementite.

[0081] Step 2: Rapid heating and quenching

[0082] The pearlite-type alloy obtained in step 1 was heated to 850°C (A) at a heating rate of 25°C / s. C3 The temperature is above 80°C) and then kept at this temperature for 600s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then it is immediately oil-quenched and cooled to room temperature to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0083] Step 3: Tempering

[0084] The quenched martensite prepared in step 2 is tempered at 350°C for 3h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0085] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2320MPa, the tensile strength can reach 2600MPa, and the elongation is 7%.

[0086] Example 5

[0087] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.59, Mn: 1.0, Si: 2.0, Cr: 0.25, Ni: 0.04, Mo: 0.27, P: ≤ 0.03, S: ≤ 0.03, and the rest is Fe.

[0088] The heat treatment process includes the following steps:

[0089] Step 1: Pre-heat treatment

[0090] The above alloy is heated to 840℃ (A C3 The sample was heated to 30°C (above 30°C) and kept at this temperature for 1.5h (the holding time was determined by 1.5min / mm), then cooled to room temperature by oil quenching to obtain a martensitic structure; then the sample was heated to 700°C and kept at this temperature for 1.5h, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure with granular Mo-rich cementite.

[0091] Step 2: Rapid heating and quenching

[0092] The pearlite-type alloy obtained in step 1 was heated to 850°C (A) at a heating rate of 20°C / s. C3 The temperature is above 50°C) and then kept at this temperature for 40s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then it is immediately oil-quenched and cooled to room temperature to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0093] Step 3: Tempering

[0094] The quenched martensite prepared in step 2 is tempered at 350°C for 3h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0095] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2316MPa, the tensile strength can reach 2560MPa, and the elongation is 6.7%.

[0096] Example 6

[0097] The invention discloses an ultrafine heterogeneous structure martensitic steel prepared based on Mo segregation, wherein the chemical composition (wt%) of the martensitic steel is: C: 0.69, Mn: 0.45, Si: 1.65, Cr: 0.96, Ni: 3.49, Mo: 0.78, P: ≤ 0.03, S: ≤ 0.03, and the rest is Fe.

[0098] The heat treatment process includes the following steps:

[0099] Step 1: Pre-heat treatment

[0100] The alloy is heated to 820°C (A C3 The sample was heated to 50°C (above 50°C) and kept for 1.5h (the holding time was determined by 1.5min / mm), then cooled to room temperature by oil quenching to obtain a martensitic structure; then the sample was heated to 700°C and kept for 5h, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite structure with granular Mo-rich cementite.

[0101] Step 2: Rapid heating and quenching

[0102] The pearlite-type alloy obtained in step 1 was heated to 850°C (A) at a heating rate of 20°C / s. C3 The temperature is above 80°C) and then kept at this temperature for 420s to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there are lamellar nano-sized Mo-rich areas in the ultrafine austenite; then it is immediately oil-quenched and cooled to room temperature to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, that is, Mo-rich martensite, Mo-poor martensite and film-like residual austenite.

[0103] Step 3: Tempering

[0104] The quenched martensite prepared in step 2 is tempered at 350°C for 3h to obtain an ultrafine heterogeneous structure tempered martensite structure, that is, a high-density coherent nanocarbide (carbide size 2-5nm) is precipitated in the nano-sized Mo-rich area, and the precipitation density of nanocarbides in the matrix is ​​relatively low.

[0105] The ultrafine heterogeneous structure martensite prepared by the alloy of this composition through the above-mentioned process heat treatment has excellent strength and plasticity. The yield strength of the alloy can reach 2430MPa, the tensile strength can reach 2656MPa, and the elongation is 6.5%.

[0106] like Figure 1As shown, an ultrafine pearlite structure is obtained based on the pearlite phase transformation, in which Mo element is enriched in the cementite lamellae and Mo is poor in the ferrite lamellae.

[0107] like Figure 2 As shown, an ultrafine granular pearlite structure is obtained based on the quenching and tempering process, in which the Mo element is enriched in the particulate cementite and the ferrite is depleted in Mo.

[0108] like Figure 3 As shown, the pearlite in which Mo is segregated in cementite obtains an ultrafine heterogeneous structure with lamellar structure characteristics after rapid heating and quenching and tempering. The white and bright lamellar layers correspond to the original cementite lamellar positions, and the dark gray lamellar layers correspond to the original ferrite lamellar positions.

[0109] like Figure 4 As shown in the figure, there are still finer martensite organizational units in the same layer, and the orientation difference of martensite in the same layer is small.

[0110] The present invention proposes a heat treatment process method for ultrafine heterogeneous martensitic steel based on Mo element segregation induction based on phase transition theory. Firstly, a Mo-alloyed alloy material system is designed, and the characteristics of pearlite structure with ultrafine structure and the property that Mo element is easily enriched in cementite are utilized. Then, an ultrafine austenite structure with uneven Mo element distribution (i.e., nano / submicron Mo-rich areas exist in ultrafine austenite) is constructed by rapid heating technology and utilizing the characteristics of slow dissolution rate of Mo-containing carbides and slow diffusion of Mo element. Then, the precipitation of carbides is regulated by quenching and tempering to construct an ultrafine heterogeneous structure, so as to solve the technical problem of difficulty in preparing large-section "ultrafine heterogeneous structure" materials and significantly improve the strength and toughness of the material.

Claims

1. An ultrafine heterogeneous martensitic steel based on Mo segregation induction, characterized in that: The Mo element is unevenly distributed in the martensitic steel, and a heterogeneous structure is formed by Mo-rich martensite and Mo-poor martensite. The size of the Mo-rich martensite is in the order of nanometer to submicron.

2. The ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 1, characterized in that: The Mo-rich martensite has higher strength, and the Mo-poor martensite has relatively lower strength but better plasticity.

3. The ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 1, characterized in that: The chemical composition of the martensitic steel is, by weight, C: 0.4-0.7, Mn: 0.3-1.0, Si: 1.0-2.0, Cr: 0.2-1.5, Ni: 0.01-3.5, Mo: 0.2-0.8, P: ≦0.03, S: ≦0.03, and the rest is Fe.

4. The ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 1, characterized in that: The Mo-rich martensite has a high density (up to 10 16 / m 3 The above) coherent nano-carbides are precipitated, while the precipitation density of coherent nano-carbides in Mo-poor martensite is relatively low, and the particle size of the coherent nano-carbides is 2-5 nm.

5. The ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 1, characterized in that: The ultrafine heterogeneous structure martensitic steel based on Mo segregation induction has a yield strength of 2000-2500 MPa, a tensile strength of 2100-2700 MPa and an elongation of 6-12%.

6. A heat treatment process for ultrafine heterogeneous martensitic steel based on Mo segregation induced according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Pre-heat treatment The alloy containing the Mo element is subjected to normalizing treatment or quenching and tempering treatment to obtain an alloy having a pearlite type structure of lamellar or granular Mo-rich cementite; Step 2: Rapid heating and quenching The alloy with pearlite structure obtained in step 1 is subjected to rapid heating austenitization treatment to obtain an ultrafine austenite structure with uneven distribution of Mo element, that is, there is a nanometer / submicron size Mo-rich area in the ultrafine austenite; and immediately subjected to quenching treatment to obtain a quenched martensite structure with ultrafine component heterogeneity, that is, Mo-rich martensite and Mo-poor martensite and film-like or granular residual austenite; Step 3: Tempering The quenched martensite structure prepared in step 2 is tempered to obtain a tempered martensite structure with ultrafine heterogeneous structure characteristics, that is, a tempered martensite structure with different carbide precipitation densities is obtained.

7. A heat treatment process for ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 6, characterized in that: For the preliminary heat treatment in step 1, it includes the following processes: Step 1) Preheating The alloy material is heated to A C3 The temperature is 30-50℃ above the workpiece and the heat preservation treatment is carried out. The heat preservation time depends on the thickness of the workpiece and is determined at 1-1.5min / mm. Step 2) Pre-heat treatment and cooling The alloy material heated in step 1) is taken out of the furnace and air-cooled to room temperature or oil-quenched to room temperature to obtain a pearlite structure or a martensite structure; Step 3) Secondary heating treatment during preheat treatment The pearlite or martensite structure obtained in step 2) is heated to 600-700°C and kept at this temperature for 1-10 hours, then taken out of the furnace and air-cooled to room temperature to obtain a pearlite type structure with lamellar or granular Mo-rich cementite, that is, the Mo element content in the cementite is significantly higher than the average Mo content of the alloy.

8. The heat treatment process of ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 6, characterized in that: The rapid heating and quenching treatment in step 2 includes the following processes: Step 1) Rapid heating and austenitization The pre-heat-treated pearlite alloy is rapidly heated to A C3 The temperature is 30-80°C above the normal temperature and kept at this temperature for 40-600s, with a heating rate of ≥15°C / s, to obtain an ultrafine austenite structure with uneven Mo element distribution, i.e., nano / submicron Mo-rich regions exist in the ultrafine austenite; Step 2) Quenching The alloy after the austenitization treatment in step 1) is immediately cooled to room temperature by oil quenching to obtain a quenched martensite structure with ultrafine heterogeneous characteristics, namely, Mo-rich martensite, Mo-poor martensite and film-like or granular retained austenite.

9. The heat treatment process of ultrafine heterogeneous martensitic steel based on Mo segregation induction according to claim 6, characterized in that: For the tempering treatment in step 3, the process is: The ultrafine heterogeneous quenched martensite structure prepared by the above process is tempered at 200-350°C for 1.5-4h to obtain an ultrafine heterogeneous structure tempered martensite structure, in which high-density coherent nanocarbides (carbide size 2-5nm) are precipitated in the nano / submicron-sized Mo-rich martensite, and the precipitation density of nanocarbides in the Mo-poor martensite is relatively low.

Citation Information

Patent Citations

  • Nano-composite martensitic steels

    CN1325685C

Cited By

  • Anti-fatigue ultra-fine grain dual-phase steel based on phase interface alloy element segregation and manufacturing process of anti-fatigue ultra-fine grain dual-phase steel

    CN119876777A

  • High-formability and high-surface-quality 2100MPa-grade cold-rolled martensitic steel for automobiles and preparation method thereof

    CN121183241A

  • A 1900mpa grade ultra-fine grain heterogeneous structure low alloy ultra-high strength steel and a preparation method thereof

    CN122811655A